2015
DOI: 10.1007/s11908-015-0483-8
|View full text |Cite
|
Sign up to set email alerts
|

The Pros, Cons, and Unknowns of Search and Destroy for Carbapenem-Resistant Enterobacteriaceae

Abstract: Antibiotic drug discovery has not kept pace with the development of microbial resistance to these agents. There are ever increasing reports where the causative agents of serious infections are multi-drug resistant and in some cases resistant to all known antibiotics. The emergence and spread of carbapenemase-producing Enterobacteriaceae has heightened awareness regarding antibiotic stewardship programs and infection prevention and control measures. There has been much controversy regarding the utility of the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Despite the inclusion of IPC and antibiotic stewardship in the Saudi Arabian strategic plan to mitigate the antibiotic resistance challenge [ 8 ], there is little information on the implementation and outcome of IPC interventions to date, particularly in healthcare facilities where elevated resistance has become endemic [ 9 ]. Knowledge of the local epidemiology of antibiotic-resistant isolates in ICU-acquired MDR-GNB could inform IPC and/or antimicrobial stewardship programs to achieve better patient outcomes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the inclusion of IPC and antibiotic stewardship in the Saudi Arabian strategic plan to mitigate the antibiotic resistance challenge [ 8 ], there is little information on the implementation and outcome of IPC interventions to date, particularly in healthcare facilities where elevated resistance has become endemic [ 9 ]. Knowledge of the local epidemiology of antibiotic-resistant isolates in ICU-acquired MDR-GNB could inform IPC and/or antimicrobial stewardship programs to achieve better patient outcomes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, more and more studies have shown that the drug resistance of AB has generally increased; the prevalence of CRAB has increased worldwide, and numerous hospital outbreaks in ICUs have been reported. [11][12][13][14] Some studies have even suggested enhanced stewardship programs are urgently needed and have been developed to avoid the spread and potential outbreaks by MDRAB, especially in high-resistance endemic settings. 15,16 Consequently, the relative efficacy of ICP and AMS is still inconclusive and controversial when it comes to controlling MDRAB and XDRAB.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Consequently, the relative efficacy of ICP and AMS is still inconclusive and controversial when it comes to controlling MDRAB and XDRAB. 11,12 Environmental cleaning (ENC) is an important component of a comprehensive strategy to control healthcareassociated infections, especially in wards such as the ICU, where patients are compromised. 17,18 One study showed that comprehensive measures with environmental cleaning in a NICU environment were effective and significantly reduced the incidence rate of methicillin-resistant Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation